2166. Preparedness for Candida auris in Canadian Nosocomial Infection Surveillance Program (CNISP) Hospitals, 2018. (26th November 2018) - Jeldes, Felipe Garcia; McGeer, Allison; Bharat, Amrita; Mitchell, Robyn
Abstract: Background: C. auris is a rapidly emerging pathogen which is potentially multidrug resistant, has caused large hospital outbreaks, and is difficult to identify in the routine microbiology laboratory. We surveyed CNISP sites to evaluate infection prevention and control (IPAC) and microbiology laboratory (MICRO) preparedness. Methods: An electronic survey with five IPAC and 12 MICRO questions was sent out to IPAC and MICRO leads for all CNISP sites in January 2018. Data were entered and analyzed in Excel. Results: We received 32 IPAC surveys representing 58/66 (88%) CNISP hospitals, and 27 MICRO surveys representing 27/32 (84%) CNISP labs. Four of 58 (7%) hospitals have a written policy for C. auris screening of patients; and 22 (38%) recommend screening; most commonly: roommates of any patient colonized/infected with any C. auris ( n = 7), room/wardmates (RWM) of patients colonized/infected with any C. auris ( n = 7) or RWM of patients with MDR C. auris ( n = 3). Without resource limitations, 50 (86%) hospitals would screen RWM of C. auris patients and 34 (59%) would screen patients previously hospitalized in the Indian subcontinent. Overall, 13/27 (48%) labs identify all clinically significant Candida spp. to the species level and 13 identify sterile site (SS) isolates. Twenty-two (81%) labs use MALDI-TOF for identification: 10 Bruker Biotyper and 12 VitekMS. 26 (96%) labs refer non-identified species and commonly misidentified yeast from SS for definitive identification. Twenty-three (85%) labs perform antifungal susceptibility testing for all Candida from blood and CSF. Twenty-two (81%) labs are confident that their current laboratory protocol would identify C. auris if the isolate is from an SS, 17 (63%) if identified as being resistant to at least 1 antifungal and 20 (74%) if the isolate is from a non-SS culture and is identified to the species level. Four (15%) labs have a protocol for C. auris colonization detection. Four labs have identified six C. auris isolates: two reported retrospective identification of three fluconazole susceptible C. auris ; and two reported one resistant and two MDR isolates identified prospectively in 2017/2018. Conclusion: MDR C. auris have been identified in Canada. Gaps remain in ensuring reliable identification of C. auris, particularly from non-SS, and most IPAC CNISP teams and MICRO do not yet have protocols for identification of C. auris colonization. Disclosures: All authors: No reported disclosures.